Eficacia y seguridad de la Ketamina en una paciente con depresión, síntomas psicóticos, enfermedad cardiovascular y riesgo de inanición - Trejos Orozco, Efraín Alberto; Gutiérrez Segura, Julio César; Ochoa Orozco, Sergio Andrés (Revista Médica de Risaralda, 2022)
Introduction: There has been a rising interest in ketamine as a promising treatment for refractory depression. Despite this, there is uncertain knowledge regarding aspects of the routinary use of ketamine for treating depression, such as optimal doses, long term toxicity, abuse potential in depressed patients, probable adverse effects associated with antidepressant drugs, the indication of ketamine in psychotic patients, and the ethical concerns of ketamine use. Clinical case: A 63 year-old woman with a psychotic depressive episode, catatonic features, cardiovascular disease (patent foramen ovale and atrial fibrillation) , and starvation risk because she refused food intake. She was sent to electroconvulsive therapy (ECT) after several weeks of oral administration of benzodiazepine, antipsychotic, and antidepressant medications; the patient presented no improvement, but she was rejected due to her cardiovascular comorbidity. Two IV Ketamine doses were used as a life-saving strategy with good clinical response, mainly in terms of the catatonic features. The ketamine treatment was not only effective but also well tolerated. Discussion: Despite the little information regarding its use in psychotic and catatonic patients, this case would suggest that it remains effective and safe, as well as a good option for patients with cardiovascular disease and those who cannot use electroconvulsive therapy.